EVALUASI PENGELOLAAN LIMBAH MEDIS PADAT BAHAN BERBAHAYA DAN BERACUN (B3) DI RUMAH SAKIT TK. II 04.05.01 dr. SOEDJONO MAGELANG - Nila Himayati; Tri Joko; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Hospital TK. II 04.05.01 dr. Soedjono Magelang is a grade B hospital which already has accreditation plenary. Health care facilities has side result was medical and non medical waste. Medical waste generated belongs to the hazardous materials and toxic waste. Hazardous and toxic medical solid waste has mandatory be well managed must be managed properly in the waste began to phase reduction and sorting, storage phase and the transport phase to reduce the risk of employment, health, and environmental impact. The purpose of this research was to evaluate the management of hospital B3 solid waste from reduction and sorting stage, the storage stage, carriage stage under Regulation Ministry of Environment and Forestry No. 56 in 2015 on Procedures and Technical Requirements for the management of hazardous and toxic of Health Care Facilities. This research is observational research which has qualitative descriptive with cross sectional approach. This research subject is taken using purposive sampling technique that consists of 9 key informants and 3 triangulation informants. The results of this research showed that the average B3 solid medical waste generated each day reach 82.37 kg. Assessment of the evaluation based on the regulation of the Minister of environment and Forestry Number 56 year 2015 get a percentage of 76,39%, which means do not meet the standard of 100%. Problems were found in the stages of management, such as there is no system of labelling on the containers and bags of waste, errors in the storage and transport, as well as negligence officer in usage self tool protection (APD) in the storage and carriage stage.